The Colors Profile of Duck Meat with Combination of Liquid Smoke Papain Enzyme Levels at Marinated - Andi Dharmawan Wicaksono; Hikmah M Ali; Nahariah Nahariah (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2021)
Duck meat is a livestock product favored by Indonesians, especially in South Sulawesi. The papain enzyme contains a proteaze enzyme that breaks down protein in meat as a meat tenderizer. Liquid smoke contains phenolic compounds as antioxidants, antibacterial agents and as a binder. The study was designed with a completely randomized design with a 5 x 5 factorial pattern with 3 replications. The first factor was the combination of papain enzyme levels and liquid smoke; factor A = (A1 = PE: 100%, A2 = LS: 25%, A3 = LS: 50%, A4 = LS 75%, A5 = LS: 100%) and the second factor was the marinated times; factor B = (B1 = 0, B2 = 30, B3 = 60, B4 = 90, and B5 = 120 minutes). There was no significant effect (P>0.05) of the combination of liquid smoke board enzyme levels on the (L*) brightness value, but at marinated time a significant effect (P<0.01) on the (L*) brightness value, especially at 120 minutes. There was no significant effect (P>0.05) from the combination of levels on the (a*) redness value, but at the time of marinated there was a significant effect (P<0.05) on the redness (a*) value, especially at 90 minutes. There was a significant effect (P<0.05) of the combined levels on the (b*) yellowness value, but at the time of marinated the significant effect (P<0.05) was on the (b*) yellowness value, especially at 90 minutes. The results showed that the addition of the combined level of the liquid smoke papain enzyme at the brightness (L*) and redness (a*) values didn’t give a significant effect, while the yellowish value (b*) gave an increase in the yellowish value at a concentration of 75% of liquid smoke. Marinated time gives a value that increases with increasing marinated times on the resulting color value. Keywords: Papain enzyme, liquid smoke, marinated times, duck meat